Advances in Nanotechnology-Based Immunotherapy for Glioblastoma - Tang, Lin; Zhang, Ming; Liu, Chaoyong (Frontiers in Immunology, 2022)
Glioblastoma (GBM) is the most aggressive type of brain tumor. Despite the multimodal treatment, the effectiveness of traditional treatments is not much satisfying. In recent years, immunotherapy has become the focus of tumor treatment. Unlike traditional treatments that directly target tumor cells, immunotherapy makes use of the body's immune system to kill tumors. However, due to the severe immunosuppressive microenvironment of GBM, it generally has a poor response to immunotherapy. In addition, the existence of the blood-brain barrier (BBB) also compromises the immunotherapeutic efficacy. Therefore, effective immunotherapy of GBM not only requires the therapeutic agents to efficiently cross the BBB but also relieves the strong immunosuppression of the tumor microenvironment of GBM. In this review, we will introduce the CNS immune system, immunosuppressive mechanism of GBM, current GBM immunotherapy, and the development of nanomaterials for GBM immunotherapy. This article will classify and summarize GBM immunotherapy based on nanomaterials, roughly divided into four parts: delivery of immune checkpoint inhibitors, targeting immune cells, combination therapy, reversing the immunosuppressive microenvironment, to provide new ideas for future GBM immunotherapy.